Book Review – Maritime Security in Southeast Asia - Amer, Ramses (Penerbit Universiti Sains Malaysia (USM Press), 2009)
This edited volume deals with issues and dimensions related to maritime security in Southeast Asia. This is of considerable interest and relevance both from scholarly and policy-making perspectives. The contributors are scholars based in Southeast Asia and a limited number of European based scholars. The volume is the end product of a two-workshop process. The volume is structured in the following way. The volume is divided into five parts and fifteen chapters. The five parts are "Introduction", "Challenges", "Responses", "Comments and reflections", and "Afterword". Chapter 1 by Anders C. Sjaastad analyses the Southeast Asian sea-lanes of communication and security options (pp. 1–13). Chapter 2 by Barry Desker discusses the safety of navigation in the Malacca Strait (pp. 14–18). Chapter 3 by Joshua Ho analyses the importance and security of regional sea-lanes (pp. 21–33). Chapter 4 by W. Lawrence S. Prabhakar is devoted to the regional dimension of territorial and maritime disputes in Southeast Asia (pp. 34-48). Chapter 5 by Ralf Emmers analyses the maritime disputes in the South China Sea (pp. 49–61). Chapter 6 by Catherine Zara Raymond is devoted to piracy in the waters of Southeast Asia (pp. 62–77). Chapter 7 by Arabinda Acharya studies the threat of maritime terrorism in Southeast Asia (pp. 78–93). Chapter 8 by Sam Bateman analyses the possibilities of creating order at sea in Southeast Asia (pp. 97–116). Chapter 9 by Robert Beckman studies the issue of Archipelagic sea-lanes passage in Southeast Asia (pp. 117–133). Chapter 10 by Christian-Marius Stryken is devoted to the Regional Maritime Security Initiative of the United States of America (USA) and its grand strategy on Southeast Asia (pp. 134–145). In chapter 11 Jan Georg Christophersen studies satellite-based tracking of ships as a global crime control (pp. 146– 161). Chapter 12 by Gunnar Stølsvik is devoted to flags of convenience and its impact on combating crime at sea (pp. 162–174). Chapter 13 by John K. Skogan analyses the challenges of terrorism at sea (pp. 177–188). In Chapter 14 Kwa Chong Guan reflects on the changing maritime security environment (pp. 189–197). Finally, in Chapter 15 Tay Lim Heng discusses the importance of shipping and the challenges ahead (pp. 201–204).